Injury as a Threat To Health, Experiences of Falling From Trees in Farmers: A Qualitative Study - Zahra Zobdeh; Saeid Bashirian; Salman Khazaei; Ensiyeh Jenabi; Maryam Afshari; Hamid Shokoohi; Mehran Biglari; Behzad Gholamaliee (Journal of Qualitative Research in Health Sciences, 2023)
Background: Falling is a significant cause of occupational injuries and fatalities among farmers, and falling from trees is one of the most common causes of injury resulting in a high number of visits to health centers. Despite this, there is limited evidence on the factors associated with falling from walnut trees. Therefore, this study aimed to identify the factors that contribute to falling from walnut trees from the perspective of farmers and farmworkers.Methods: This qualitative study was conducted using conventional content analysis. Data were collected through semi-structured interviews with 20 farmers and farmworkers who had experienced falling from walnut trees as recorded in the National Accidents Record Program from September to October 2017 in Tuyserkan county, Iran. Participants were selected through purposive sampling. Moreover, data rigor was ensured through participant and external checks. All interviews were recorded and analyzed using content analysis methods.Results: Data analysis led to the extraction of six themes, including psychological factors, physical factors, behavioral and habitual factors, economic factors, factors related to walnut trees, and atmospheric agents, along with 18 subthemes for behavioral, human, and environmental factors.Conclusion: The findings of this study suggest that with appropriate interventions and training, farmers and farmworkers can be guided and assisted so as to prevent the occurrence of falling from walnut trees. In addition to educational interventions, health promotion measures such as providing safety equipment and insurance coverage can be essential in reducing injuries.